Abnormal uterine bleeding and fertility challenges secondary to long COVID: A case report - Adrianna Clapp; Dani Zapp; Thomas DeLuca; Anjali Morris; Shin jie Yong; Ridwan Ahmad; Bala Munipalli (SAGE Open Medical Case Reports)
Menstrual irregularities and abnormal uterine bleeding have been increasingly reported following severe acute respiratory syndrome coronavirus 2 infection, likely due to viral-induced endocrine disruption and immune dysregulation. A woman in her late 30s, with previously regular menses, developed persistent abnormal uterine bleeding after recovering from coronavirus disease 2019. Lab work-up over the next 2 years demonstrated high follicle-stimulating hormone, low anti-Müllerian hormone, low estrogen, and borderline antinuclear antibody titers. A pelvic ultrasound showed low antral follicle count, and she had challenges with fertility preservation. The patient was suspected of having an exaggerated immune reaction to severe acute respiratory syndrome coronavirus 2 infection with her strong family history of autoimmune disease and borderline antinuclear antibody, which may have led to an autoimmune-induced premature ovarian insufficiency. This case highlights the need to recognize post-viral menstrual irregularities and endocrine dysfunction as a potential consequence of coronavirus disease 2019. Clinicians should consider postinfectious endocrine disturbances in patients with new-onset abnormal uterine bleeding or infertility and evaluate for immune-mediated mechanisms when appropriate. Further research is needed to elucidate the long-term impact of coronavirus disease 2019 on reproductive health.